Effects of a 6-Week Internet-Based Stress Management Program on Perceived Stress, Subjective Coping Skills, and Sleep Quality - Stächele, Tobias; Domes, Gregor; Wekenborg, Magdalena; Penz, Marlene; Kirschbaum, Clemens; Heinrichs, Markus (Frontiers in Psychiatry, 2020)
Occupational stress management intervention programs are known to be effective in preventing stress-related health burden. Two essential mechanisms underlie this effect: (i) a reduction in perceived stress (e.g., via relaxation-oriented techniques), and (ii) an improvement in coping skills (e.g., via cognitive-behavioral interventions). While relaxation-oriented interventions are more frequently employed in occupational settings, cognitive-behavioral stress management interventions reveal stronger effects on stress-related outcomes. As an effective and economic strategy, the dissemination of stress management programs via the internet is soaring, but most internet-based programs focus on relaxation or reducing perceived stress. In the present study, we examined the effects of a self-guided, cognitive-behavioral 6-week Internet-Based Stress Management program (IBSM) on perceived stress, coping skills, emotional exhaustion, depressive symptoms, and sleep quality. The IBSM consists of six modules focusing on the improvement of stress management skills such as dealing with acute stress, building up resources, or reappraising stress-facilitating cognitions. The participants have to work through the content on a weekly basis, requiring about 30 min per week followed by a transfer task lasting another 30 min. Healthy employees reporting elevated stress were recruited over the internet and then randomly assigned to the IBSM group or a waiting list control group. A total of 134 participants completed all assessments before and after the training or waiting period. The IBSM group reported lower subjective stress levels after the program than the control group. In addition, the IBSM group exhibited improved coping skills and better sleep quality. Emotional exhaustion was reduced in both groups, while depressive symptoms did not change. These results suggest that a brief, 6-week, cognitive-behavioral internet-based stress management program improves coping skills, sleep quality and well-being, and reduces the perceived stress of employees. Our results might encourage large-scale studies on the long-term stability and clinical efficacy of this internet-based program. The trial is registered in the German Clinical Trials Register (DRKS00014837) URL. https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00014837